2020
DOI: 10.21203/rs.3.rs-66766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 ICU and Mechanical Ventilation Patient Characteristics and Outcomes - A Systematic Review and Meta-analysis

Abstract: Background To characterize COVID-19 ICU admissions, their outcome and associated features, as well as identify their regional discrepancies. Methods Scopus, Embase, preprint servers bioRvix and medRvix and the Intensive Care National Audit and Research Center (ICNARC) website was searched for reports through May 1st 2020 on COVID-19 ICU admissions and outcomes using pre-defined search terms and eligibility criteria.Relevant data was extracted and pooled using fixed or random effects meta-analysis depending on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 56 publications
4
41
2
4
Order By: Relevance
“…A meta-analysis study compiling data from several countries showed broad variability in ICU admission, IMV requirement and IMV mortality rates [31]. Brazilian COVID-19 patients ICU admission rate (39.37%) was similar a USA patients (35%).…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis study compiling data from several countries showed broad variability in ICU admission, IMV requirement and IMV mortality rates [31]. Brazilian COVID-19 patients ICU admission rate (39.37%) was similar a USA patients (35%).…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis study compiling data from several countries showed broad variability in ICU admission, IMV requirement and IMV lethality rates [ 34 ]. Brazilian COVID-19 patients ICU admission rate (39.37%) was similar to USA patients (35%).…”
Section: Discussionmentioning
confidence: 99%
“…The need for IMV varied widely, from 29.1% to 89.9%, among patients admitted to the ICU with COVID-AHRF. IMV is invariably associated with high mortality ranging from 16% to 78% ( 2 , 4 , 31 , 36 , 37 ). Very few studies have assessed the impact on the mortality of the mode of respiratory support in severe forms of COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%